Ilmenite as alternative bed material for the combustion of coal and biomass blends in a fluidised bed combustor to improve combustion performance and reduce agglomeration tendency - Garcia, Eduardo; Liu, Hao (Energy (Oxford), 2022)
Co-firing coal and biomass has the potential to reduce GHG emissions. However, high levels of alkali and alkaline metals in biomass ash can bring additional issues to the operation of coal-fired boilers. This study investigates the effects of ilmenite as the bed material on CO and NOx emissions and combustion efficiency of a coal and biomass blend, and the agglomeration tendency of the bed material with a pilot-scale (30 kWth) bubbling fluidised bed combustor. The experiments were carried out at 900 °C using a bituminous coal blended with wheat straw pellets at 40 wt% as the fuel and silica sand as the baseline bed material. Samples of agglomerates collected from the combustor and cyclone ash were characterised by SEM-EDS, XRD, and XRF. The results revealed that ilmenite could reduce the level of excess air required to achieve complete combustion due to lower CO emissions and less efficiency loss compared to silica sand. However, ilmenite increased NOx emissions. Furthermore, the characterisation of the obtained agglomerates and cyclone ash showed that ilmenite could hinder the K-rich molten substance attachment to the bed material, leading to significantly smaller agglomerates and hence less tendency towards defluidisation in comparison to silica sand. •Coal and biomass co-combusted in a pilot-scale (30 kWth) bubbling fluidised bed.•Ilmenite as bed material led to lower CO emissions and less efficiency loss.•Less and smaller agglomerates were found when ilmenite was used as the bed material.•Ilmenite could reduce the tendency of agglomeration and defluidisation.•Ilmenite improves combustion performance of coal and biomass blends.